The effective of cold compress in reducing pain before insertion of IV or blood draw in school-age children: Kompres Dingin Efektif dalam Mengurangi Nyeri Sebelum Pemasangan Infus atau Pengambilan Darah pada Anak Usia Sekolah - Dais, Exsos Grend; Lusty, Junita; Karwati, Eti; Purwati, Nyimas Henry (Riset Informasi Kesehatan, 2025)
Background: The invasive procedure of insertion of IV or blood draw is carried out by inserting a needle into a vein, causing pain in the child. As a result, children find it difficult to interact with other people, have difficulty sleeping, decrease their interest in doing activities, and increase anxiety. One non-pharmacological measure to reduce pain is giving a cold compress using a cool gel pack. Method: The purpose of this study was to determine the effect of cold compress on pain during insertion of IV or blood draw in school-age children. Respondents in this study were school-age children (7-12 years) who were given a cold compress before insertion of IV or blood draw in the insertion of IV area which was divided into 2 groups, namely the intervention group with 20 respondents and the control group with 20 respondents. The research design used Quasy Experiment with Two Group Post Test Design. Results: The research results were obtained the pain measurement tool using the Numerical Rating Scale in the intervention group was in the mild pain category (1-3) as many as 18 (90%), while in the control group it was in the severe pain category (7-10) as many as 20 (100%),so it can be concluded that there is an effect of cold compress on pain during insertion of IV or blood draw in school-aged children with p-value: 0.000 (p<0.05). Conclusion: It is recommended for hospitals to continue cold compress interventions to reduce pain during insertion of IV or blood draw and provide education so that parents can recognize the importance of cold compress in pediatric pain management.